Factors related to recurrence in non-obese women with endometrial endometrioid adenocarcinoma - Panggid K. (2014)
Aim: To evaluate the clinicopathological factors associated with recurrence of disease in non-obese women with endometrial endometrioid adenocarcinoma. Methods: Medical records of the 138 patients who had newly diagnosed endometrial endometrioid adenocarcinoma with body mass index (BMI) <25 and underwent a complete staging surgery between 1999 and 2007 were reviewed. Results: The median age was 55 years (30-75 years). The median BMI was 21.3 (14.0-25.0). The International Federation of Gynecology and Obstetrics (FIGO) (1988) stages of the patients were as follows: 11 (8.0%) Ia, 30 (21.7%) Ib, 23 (16.7%) Ic, 5 (3.6%) IIa, 13 (9.4%) IIb, 12 (8.7%) IIIa, 2 (1.4%) IIIb, 38 (27.5%) IIIc, 4 (2.9%) IVb. Lymphovascular space invasion (LVSI) and lymph node metastasis was present in 73 (53%) and 38 (27.5%) patients, respectively. LVSI was significantly correlated with lymph node metastasis (P < 0.0001), advanced FIGO stage (P < 0.0001), poor histological grade (P = 0.006), and deep uterine invasion (P < 0.0001). The presence of LVSI, poor histological grade, and advanced stage were found significantly in patients who had disease recurrences (P = 0.026, P < 0.001, and P = 0.015, respectively). Patients with LVSI, when stratified by FIGO stage, had a significant lower 5-year overall survival rate (58.8% versus 76.3%, log-rank test, P = 0.04). Conclusion: LVSI, poor histological grade, and advanced stage were associated with disease recurrence in non-obese women with endometrial endometrioid adenocarcinoma. Non-obese patients with LVSI-positive tumors tend to have a poorer survival rate than obese patients with LVSI-positive tumors. © 2010 Japan Society of Obstetrics and Gynecology.